USING WIKISPACES TO IMPROVE STUDENTS’ WRITING NARRATIVE TEXT - Eka Yuliani saputri; Tauricha Astiyandha (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
The research consists of two variables, namely the independent variable (wikispaces) and the dependent of variable (writing narrative text). The purpose of this research is to find out whether or not there is effect between using wikispaces and writing narrative text. This research was conducted on grade ten students at SMA Islam As-Syafi’iyah 02, Pondok Gede, Bekasi in academic year of 2016-2017. Research method used in this research quantitative and the design quasi experimental post-test only. To collect data the researcher used one instrument in the form of subjective, essay writing each numbering five question for both experimental and control class and also tried out in class at SMA Islam As-syafi’iyah 02, Pondok Gede, Bekasi. The scores obtained from the try-out classes were used to analyse the validity, reliability, discrimination power and difficulty index of each question item in two one instruments. The population of this research was grade ten students consisting of 142 students occupying 5 classes. The number of samples was 30 students as control class and 30 students as experimental class taken from the population using cluster random technique. The results obtained from samples were used to analyse the data using statistical formula of Anova One Way, preceded by normality and homogeneity test as the pre-requisite requirement for data analysis. The analysis using SPSS 23 version- based normality significance (Sig.) value of 0.200 > 0.05. and the significance value of homogeneity is 0.210 > 0.05. and the result of Anova one way 0.03 < 0.05, it means the H0 is rejected and HA was accepted. So, there is significance of using wikispaces media on grade ten students’ writing narrative text at SMA Islam As- Syafi’iyah 02. The result of the study revealed that the wikispaces outperformed the traditional writing class. Based on the obtained data dealt with in details in the study, it could be understood that the use of wikispaces would enable writing students to perform better.